Autism spectrum disorder and PTEN hamartoma tumor syndrome â Child and adolescent psychiatric perspective - Marta P. Antunes; Natália Tkachenko; Ana R. Soares; Graça Fernandes; Ana M. Fortuna; Célia Azevedo-Soares (Publicaciones Permanyer, 2024)
Introduction: Autism spectrum disorder is a neurodevelopmental disorder characterized by impairments in social communication and social interaction and the presence of restricted, repetitive patterns of behavior, interests, or activities that negatively impact social, occupational, or other domains. Certain clinical features in autism spectrum disorder patients could raise suspicions of a syndromic form, such as PTEN hamartoma tumor syndrome, which is also associated with cancer predisposition in adulthood, in child and adolescent psychiatric appointments. Case report: Three pediatric patients with autism spectrum disorder presented clinical features in their physical examination that elicited a suspicion of PTEN hamartoma tumor syndrome. Their autism spectrum disorder profile was indistinguishable from idiopathic autism spectrum disorder and did not contribute to clinical pre-test suspicions of PTEN hamartoma tumor syndrome. Discussion: PTEN hamartoma tumor syndrome features should be screened in autism spectrum disorder patients to provide further medical care, including appropriate cancer screening.